Differences in Blood Glucose Levels Between POCT (Point of Care Testing) and Spectrophotometer Methods - Khasanah, Fitri Yatun; Suparyati (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Blood glucose is a sugar found in the blood that is formed from carbohydrates in food and stored as glycogen in the liver and muscles. Glucose is one of the important carbohydrates used as the main source of energy in the body. Blood glucose test results exceeding the normal level of 200 mg/dl may indicate that a person has diabetes mellitus. This study aims to determine the difference in blood glucose levels between the POCT method and the spectrophotometer. Method: The study design is analytical, using random sampling with 30 participants, and statistical analysis was performed using the Paired T-Test and Wilcoxon test. Result: The results of this study using the Paired T-Test showed that POCT data is normally distributed (sig value = 0.208 > 0.05), while spectrophotometer data is not normally distributed (sig value = 0.003 < 0.05). Meanwhile, the Wilcoxon test yielded a sig value of 0.000 < 0.05. Conclusion: The results of blood glucose level measurements using the POCT method showed an average value of 128.83 mg/dl, while the spectrophotometer results showed an average value of 88.07 mg/dl. Based on the statistical test results, the sig value was 0.000 (p<0.5), meaning H0 was rejected. This means that the difference between the two measurement methods is statistically significant.